Impact of workshop on emergency care management: Nursing perspectives on the knowledge of nursing staffs - Kumar, Ashok; Maul Jacob, Bindu; deep Kaur, Maninder; Nagi, Manisha; Kaur, Jaspal (International Journal of Nursing Research, 2023)
Introduction: Trauma and emergency care in a department is critically dependent on the training and competence of the health care professionals posted there. Nurses play a crucial role in providing care in emergency conditions. The current study was planned to study Impact of workshop on “Emergency Care Management: Nursing Perspectives” on the knowledge of Nurses working in PGIMER, Chandigarh.” Nurses working in the emergency require in-service training in order to update them regarding the latest development in nursing practice. Material and methods: This pre-experimental was conducted on 166 nursing officials of PGIMER, Chandigarh, who were willing to participate in the workshop by using total enumeration technique. An objective type of questionnaire validated by experts was used to assess the knowledge before and after the teaching programme. Paired t test was applied to compare before and after knowledge score of nurses on the emergency care management. McNemar matched pair was applied to compare the percentage of the correct response of each question before and after workshop. Results: Total 166 subjects were participated in the study out of which 82% were female nursing officials while 18% of the participants of the workshop were male nursing officials. The mean age of the participants was 34.60 ± 10.13 years with the range of 22- 59 years. There were 82% female nursing professionals. Mean pre-workshop scores of female and male nurses were 15.90±3.86 and 13.33±3.41, respectively. Mean post workshop scores of female and male nurses were 20.24±2.84 and 22.63±2.48, respectively. Conclusion: There was significant increase in the mean knowledge score after workshop among male and female participants. So we can conclude that there should be organization of such type of workshops to improve the knowledge of in-service staff to equip them with latest news.